Evaluasi Aplikasi Simen Sebagai Media Pembelajaran Menarche pada Kader PKK di Desa Kemuning Lor Jember - Bakhtiyar Hadi Prakoso; Gandu Eko Julianto Suyoso; Veronika Vestine; Dina Fitriyah; Surya Dewi Puspita; Angga Rahagiyanto (Puslitbang Sinergis Asa Professional, 2023)
Menarche is the first menstruation that occurs in young women. Knowledge about menarche will be an important provision for young women in facing menarche and the next menstrual period. Dissemination of valid information regarding menarche can be facilitated using information technology in the 4.0 revolution era, one of which is the Simen application. Simen applications, like other applications/software, need to be evaluated. Evaluation will show the advantages and disadvantages of an application, which will become the basis for further development of an application. The evaluation method used is usability analysis with 5 variables (learnability, memorability, efficiency, error and satisfaction). The instrument used was a questionnaire addressed to 20 Simen application users. The results of the questionnaire showed that the variable memorability (average score of the questionnaire was 4.15), the variable efficiency (the average value of the questionnaire was 4.07), and the error variable (the average value of the questionnaire was 4.10) was good. Meanwhile, the learnability variable (the average value of the questionnaire is 3.24) and the satisfaction variable (the average value of the questionnaire is 3.56) is sufficient. Based on these results, the Simen application still requires further improvements regarding the user interface and content.in the abstract.